Bentonite functionalized with magnetite nanoparticles synthesized from mining sludge: a new magnetic material for removing iron and manganese ions from water - Lima, Andre A. A.; Quirino, Juliana N.; Cavina, Rafael; Onishi, Bruno S. D. [UNESP]; Santos, Maria J. (Springer Nature, 2023)
Abstract: Magnetite nanoparticles (17.07±1.89 nm) were synthesized from mining sludge (Mag-NPR) by co-precipitation with ammonium hydroxide. Mag-NPR was used in bentonite coating (B-Mag) for removing iron (Fe) and manganese (Mn) ions from water. Mag-NPR and B-Mag were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, nitrogen physisorption, and scanning electron microscopy. Structural similarity of both materials was observed compared to conventional standards from literature. The maximum sorption capacity in B-Mag was 1.43 × (Fe) and 3.30 × (Mn) higher when compared to bentonite, indicating that the synthesized material is effective in removing Fe(II) and Mn(II). The mobilization factors of Fe(II) and Mn(II) were 96.6% and 24.3% for B-Mag and 36.2% and 26.9% for bentonite. Competitive sorption showed maximum Fe(III) and Mn(II) sorption capacities exceeding 4.5 and 2.0 times as much as in the single mode. The new magnetic properties make the B-Mag reusable and easily separated from the aqueous solution, removing color, smell, and turbidity while removing Fe and Mn ions, with remarkable technological potential. Graphical abstract: Iron mining sludge accidentally spilled into the Rio Doce basin - MInas Gerais state - Brazil.[Figure not available: see fulltext.].
Keywords: Health and safety effects; Magnetic nanoparticles; Magnetism; Metal removing; Mining residue; Sorption